Applying Importance Performance Analysis (IPA) Method in Analyzing Level of Service Quality - Firda Auliawati Nuraieni; Nanda Ravenska; Hafid Aditya Pradesa (Jurnal Ilmu Manajemen Advantage, 2021)
The more the startups are established in Indonesia, the higher the competition for companies in offering their products and services to customers. In overcoming increasingly fierce business competition, Bliin always makes efforts to improve the quality of service on its application with the aim of creating customer satisfaction. This research employed a descriptive, quantitative method. The population in this study comprises the users of Bliin application who have made transactions and live in Bandung City. the sample used amounted to 191 respondents. The data were collected through questionnaires. The analysis method used the Gap analysis and Importance Performance Analysis (IPA). Based on the Gap analysis method, the overall Gap average value shows the results (-0.43) However, from the overall value per attribute item, almost all attributes are negative. There are only three attribute items that are positive. On the overall average value of the level of performance of (3.73) is smaller than the level of importance or expectation of (4.16). This indicates that the perceived service < the expected service which means that the perceived performance is not as expected. From the results of the IPA analysis method on the Cartesian diagram mapping, there are 9 attributes in quadrant I (high importance and low performance) and 8 attributes in quadrant II (high importance and high performance).